Copyfight: The Global Politics of Digital Copyright Reform - BLAYNE HAGGART (University of Toronto Press, 2014)
Studying copyright, especially if youâ€™re not a lawyer, is akin to stepping into a madhouse where things barely adhere to any internal logic, let alone traditional standards of what makes good public policy. As an economist cum political scientist, I found recent calls for â€œevidencebasedâ€ copyright policy to be a bit stunning: itâ€™s a three-hundred-yearold policy and only now weâ€™re starting to ask for evidence? Thatâ€™s the copyright debate in a nutshell. Copyright and intellectual property lawmaking often involve the exercise of power and influence justified in terms of foundational Western concepts like the individual and property. No wonder Cory Doctorow and others refer to the â€œcopyfight.â€1 Itâ€™s politics laid bare